An Overview of Cell-Based Assay Platforms for the Solute Carrier Family of Transporters - Dvorak, Vojtech; Wiedmer, Tabea; Ingles-Prieto, Alvaro; Altermatt, Patrick; Batoulis, Helena; Bärenz, Felix; Bender, Eckhard; Digles, Daniela; Dürrenberger, Franz; Heitman, Laura H.; IJzerman, Adriaan P.; Kell, Douglas B.; et al. (Frontiers in Pharmacology, 2021)
The solute carrier (SLC) superfamily represents the biggest family of transporters with important roles in health and disease. Despite being attractive and druggable targets, the majority of the SLCs remains understudied. One major hurdle in research on SLCs is the lack of tools, such as cell-based assays to investigate their biological role and for drug discovery. Another challenge is the disperse and anecdotal information on assay strategies that are suitable for SLCs. This review provides a comprehensive overview of state-of-the-art cellular assay technologies for SLC research and discusses relevant SLC characteristics enabling the choice of an optimal assay technology. The Innovative Medicines Initiative consortium RESOLUTE intends to accelerate research on SLCs by providing the scientific community with high-quality reagents, assay technologies and data sets, and to ultimately unlock SLCs for drug discovery.